Book review: Taylor, C. (2012). Empathic Care for Children with Disorganised Attachments: A Model for Mentalizing, Attachment and Trauma-Informed Care - Nicola Kieran (Scottish Journal of Residential Child Care)
If you work in residential childcare, it seems likely that you will be supporting young people who have experienced traumatic events in their childhood. It is known that such experiences have a significant impact on brain development and the quality of attachment with their care givers (Cairns, 2015, p.50). You might think that there is little you can do to help them recover from their experiences. You might think that your young people have come into residential childcare too late; that the potential for therapeutic working is long gone. Chris Taylor suggests otherwise: he suggests that with understanding and empathy, young people can heal.